A sketch grammar of Singapore Foochow - Thang, Marcus Guo Ping (Nanyang Technological University, 2020)
This is a sketch grammar of Foochow, specifically, the variety that is spoken in Singapore. Foochow is an Eastern Min (or East Fujian) language, which is also widely known as a dialect, both in China and in Singapore. This paper aims to give the reader a broad understanding of the linguistic features of this variety in terms of its phonology, grammar, and lexical features. It is by no means a fully comprehensive description of Foochow though through inductively analysing mainly data gathered by recording native speakers of the language, the author hopes to have this paper as a springboard to further research into this dying language. The terms language, dialect, and variety are used interchangeably to refer to Singapore Foochow, as the author does not address the socio-political issues relating to the terms.